101 Motor and non-motor features of prodromal PD. Issue 9 (12th August 2022) - Rees, Richard; Simonet, Cristina; Gill, Aneet; Giovannoni, Gavin; Bestwick, Jonathan; Lees, Andrew; Noyce, Alastair; Schrag, Anette
Abstract : Introduction: A range of non-motor features can be evident at the point of diagnosis of Parkinson's disease (PD). Objectives: To identify non-motor features of prodromal PD in participants from the PREDICT-PD study. Methods: Higher-risk (HR) (odds of PD >1:30) and matched lower-risk (LR) participants from PREDICT-PD and PD patients underwent validated clinical assessments, in which the assessor was blinded to risk scores, including MDS-UPDRS I-III, other functional motor tasks, and standardised assessments of cognition, autonomic function, pain and sleep. Results: 28 LR, 31 HR and 22 PD patients were examined. HR participants were more impaired than LR in all motor tasks, as well as the SCOPA-AUT, PD Sleep scale, HADS and MDS-UPDRS I & II. There were no sig- nificant differences between HR and PD, other than for the MDS-UPDRS part II, part III, the gastrointestinal sub-score of the SCOPA-AUT, and measured orthostatic hypotension. In all domains tested there was a relationship between the log odds of PD risk and dysfunction using linear regression. Conclusion: This study provides strong evidence that non-motor features are prominent in at-risk indi- viduals, as well as mild motor impairment, and that these symptoms and signs are similar to patients with established PD. Further follow-up will establish which patients develop the cardinal motor signs necessary for a clinical diagnosis of PD.